Timing of orthodontic treatment: early or late - does it matter? - Grave Keith C. (Sciendo, 1984)
The objective of this paper is to clarify the perplexing question of when to start treatment. Timing of orthodontic treatment should focus on individual maturation and family patterns. It will simplify treatment, and minimize co-operation problems, and as a consequence it will keep the orthodontist and his patient happy.